The Imidazacridine Derivative LPSF/AC-05 Induces Apoptosis, Cell Cycle Arrest, and Topoisomerase II Inhibition in Breast Cancer, Leukemia, and Lymphoma - de Oliveira Chagas, Mardonny Bruno; Mendonça da Costa, Valécia de Cássia; Montenegro, Claudio; de Lima, Maria do Carmo Alves; Melgarejo da Rosa, Michelle; Pereira, Michelly Cristiny; de Melo Rêgo, Moacyr Jesus Barreto; da Rocha Pitta, Maira Galdino (Current Cancer Drug Targets, 2025)
IntroductionCancer is one of the major causes of morbidity and mortality worldwide. Current treatments for both solid and hematological tumors are associated with severe adverse effects and drug resistance, necessitating the development of novel selective antineoplastic drugs.MethodsThe present study describes the antitumor activity of the imidazacridine derivative 5-acridin-9-ylmethylidene-2-thioxoimidazolidin-4-one (LPSF/AC05) in breast cancer, leukemia, and lymphoma cells. Cytotoxicity assays were performed in PBMC and in breast cancer, leukemia, and lymphoma cell lines using the MTT method. Changes in cell cycle progression and apoptosis were assessed using flow cytometry. Moreover, topoisomerase II inhibition assays were performed. LPSF/AC05 exhibited cytotoxicity in six of the nine cell lines tested.ResultsThe best results for leukemia and lymphoma were observed in the Toledo, Jurkat, and Raji cell lines (IC50 = 27.18, 31.04, and 33.36 μM, respectively). For breast cancer, the best results were observed in the triple-negative cell line MDA-MB-231 (IC50 = 27.54 μM). The compound showed good selectivity, with no toxicity to normal human cells (IC50 > 100μM; selectivity index > 3). Cell death was primarily induced by apoptosis in all cell lines. Furthermore, LPSF/AC05 treatment induced cell cycle arrest at the G0/G1 phase in leukemia/lymphoma and at the G2/M phase in breast cancer. Finally, topoisomerase II was inhibited.ConclusionThese results indicate the potential application of LPSF/AC05 in cancer therapy.
Keywords: LPSF/AC05